Immune checkpoint inhibitors: Navigating a new paradigm of treatment toxicities. Issue 4 (12th July 2017) - Roberts, Kate; Culleton, Vanessa; Lwin, Zarnie; O'Byrne, Kenneth; Hughes, Brett GM
Abstract: Immune checkpoint inhibitors have recently emerged as an exciting new treatment paradigm across a broad spectrum of malignancies. This new class of agents also challenges oncologists with a unique set of immune‐based toxicities. Early recognition and precise management of these toxicities can result in better outcomes, with minimization of toxicity and harm to the patient. This article provides a comprehensive review of immune‐based toxicities caused by immune checkpoint inhibitors, including recommendations for their investigation and guidelines for specific management.